25. Zapisz w jak najprostszej postaci:₂
a) (a+b)-(2a-b)-(a-2b)
b) (3x-y+1)-(x+y)+(y-x)
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)
d) (2ab+a+3)-(3ab-a+3)
e) (4x²-3x)-(x+0,1x²)-(x²-0,1x)

29.Zredaguj wyrazy podobne:
a) a³+2a-a²+3a²-10a³+5
b)5x²-x²+y²+y-3-y+(-2)y²+5
c)13x+7y-10x-4y+5y
d) 90x+3y-x²-9•9x-2y+x²

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-10T19:47:20+02:00
A) (a+b)-(2a-b)-(a-2b)=a+b-2a+b-a+2b=-2a+4b
b) (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
d) (2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-ab+2a
e) (4x²-3x)-(x+0,1x²)-(x²-0,1x)=4x²-3x-x-0,1x²-x²+0,1x=2,9x²-3,9x

a) a³+2a-a²+3a²-10a³+5=-9a³+2a²+2a+5
b)5x²-x²+y²+y-3-y+(-2)y²+5=4x²-y²+2
c)13x+7y-10x-4y+5y=3x+8y
d) 90x+3y-x²-9•9x-2y+x²=90x+3y-x²-81x-2y+x²=9x+y
138 4 138
2010-04-10T19:53:25+02:00
25.
a) (a+b)-(2a-b)-(a-2b)= a+b-2a+b-a+2b= 4b-2a
b) (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x= x-y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
d) (2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-ab+2a
e) (4x²-3x)-(x+0,1x²)-(x²-0,1x)=4x²-3x-x-0,1x²-x²+0,1x=2,9x²-3,9x

29.
a) a³+2a-a²+3a²-10a³+5=-9a³+2a²+2a+5
b)5x²-x²+y²+y-3-y+(-2)y²+5=4x²-y²+2
c)13x+7y-10x-4y+5y=3x+8y
d) 90x+3y-x²-9•9x-2y+x²=9x+y
45 3 45